Impact of the Allergy Clarification for Cefazolin Evidence-based Prescribing Tool on Receipt of Preferred Perioperative Prophylaxis: An Interrupted Time Series Study. (4th May 2020) - Lam, Philip W; Tarighi, Payam; Elligsen, Marion; Nathens, Avery B; Riegert, Daniel; Tarshis, Jordan; Leis, Jerome A
Abstract: Implementation of a perioperative allergy and antibiotic assessment tool in patients with reported beta-lactam allergy resulted in a pronounced and sustained increase in perioperative cefazolin use. This intervention could result in improved efficiencies surrounding perioperative antibiotic administration and possible reductions in surgical site infection rates.